Effect of drought stress on the foraging behavior of insect pollinators and the reproductive success of canola (Brassica napus L.) - Younas, Muqaddas; Ali, Mudssar; Matloob, Amar; sajjad, Asif; Tahira Gul, Hafiza; Saeed, Shafqat (Emirates Journal of Food and Agriculture, 2022)
To appraise the effect of drought stress on the foraging behavior (visitation frequency and visitation rate) of insect pollinators and its ultimate impact on reproductive success of canola (Brassica napus L.), an experiment was carried out at the Research Farm of MNSUniversity of Agriculture, Multan, Pakistan. Previously, only a few studies have evaluated drought stress as a predictor of plant-pollinator interactions. Normal irrigated and drought stress plots of canola were separated by a distance of fifteen meters. Normal irrigated plots received recommended number of irrigations (three times) i.e., 1st irrigation at 30 days after germination (DAG), 2nd at flowering, and 3rd at pod setting. However, irrigation was applied only once to drought-stressed plots i.e., 1st irrigation at 30 DAG. Twelve insect species in two orders and five families visited the canola flowers. These floral visitor species were grouped into three categories, i.e., Apis bees (honey bees), non-Apis bees, and flies. The abundance of Apis and non-Apis bees was significantly higher in irrigated plots than in drought plots, while the abundance of flies did not differ significantly in both plots. Stay time of all the floral visitors was significantly higher in drought plots, while the visitation rate was significantly higher in irrigated plots. The interaction between pollination modes (open pollination and self-pollination) and water regimes (normal irrigation and drought stress) was significant for all the reproductive success parameters of canola (silique length and weight, number of seeds per silique, seed weight per silique, number of siliques per plant and fatty acid contents (%) of canola seeds) under normal irrigation regime for free insect visits treatment. Moreover, a variation of 83% to 207% was observed for these parameters between irrigated and drought plots receiving insect pollination (free insect visits) due to higher pollinator abundance and visitation rate in the former ones. However, all the reproductive success parameters did not vary between irrigated and drought plots with no insect pollination (no insect visits, caged treatment). In conclusion, drought stress negatively affected insect pollinators’ foraging behavior, leading to low reproductive success in canola. In the climate change scenario and limited water availability, future studies should consider drought stress for other cross-pollinated crops under varying environments and pollinator fauna.